Anything but plain - Fisher, Suzanne Woods (Revell, a division of Baker Publishing Group, 2022)
"Impulsive and unreserved, Lydie Stoltzfus has always felt like a disappointment-a square peg in a round hole in her quiet Amish community. Leaving Stoney Ridge seems like her best move -- even though it would mean leaving Nathan Yoder behind." --